All the bright places the story of a girl who learns to live from a boy who wants to die - Niven, Jennifer (New York, USA Penguin random house company, 2015)
Theodore Finch is fascinated by death. Every day he thinks of ways he might kill himself, but every day he also searches for$1 (Band manages to find$1 (Bsomething to keep him here, and alive, and awake. Violet Markey lives for the future, counting the days until graduation, when she can escape her small Indiana town and her aching grief in the wake of her sister$1 (Bs recent death. When Finch and Violet meet on the ledge of the bell tower at school$1 (Bsix stories above the ground$1 (Bit$1 (Bs unclear who saves whom. Soon it$1 (Bs only with Violet that Finch can be himself. And it$1 (Bs only with Finch that Violet can forget to count away the days and start living them. But as Violet$1 (Bs world grows, Finch$1 (Bs begins to shrink. . . .s
Keywords: English Fiction